2021
DOI: 10.1111/jpm.12717
|View full text |Cite
|
Sign up to set email alerts
|

“Can mental health nurses working in acute mental health units really be trauma‐informed?” An integrative review of the literature

Abstract: The term trauma, from the Greek word meaning "wound," was originally used to refer to an injury of the body. More recently, it has also been applied to include experiences that are psychologically distressing or disturbing (Oxford University Press, 2018). A traumatic event is defined as an actual or threatened death, injury, or violence (American Psychiatric Association, 2013). Complex trauma refers to a type of trauma that occurs repeatedly and cumulatively, usually over a period and within specific relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
(230 reference statements)
0
7
0
Order By: Relevance
“…Much of the discourse around MHN is centred around a highly vulnerable workforce, with imminent workforce shortages, insufficient resources, high rates of workplace violence and aggression, substance use and unpredictably unsafe environments (Cranage & Foster, 2022). Previous TIC studies have highlighted the urgency for a critical review into MHN experiences of compassion fatigue, vicarious trauma and the subsequent implications for TIC (Wilson et al, 2021). Very few studies have explored the positive or affirmative processes that support the proliferation of TIC in lieu of the abovementioned challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the discourse around MHN is centred around a highly vulnerable workforce, with imminent workforce shortages, insufficient resources, high rates of workplace violence and aggression, substance use and unpredictably unsafe environments (Cranage & Foster, 2022). Previous TIC studies have highlighted the urgency for a critical review into MHN experiences of compassion fatigue, vicarious trauma and the subsequent implications for TIC (Wilson et al, 2021). Very few studies have explored the positive or affirmative processes that support the proliferation of TIC in lieu of the abovementioned challenges.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only four reviews have explored TIC from the perspective of the MHN in the acute mental health environment or hospital setting, with many of the cited studies within these reviews being outdated and lacking robust methodological rigour (Muskett, 2014; O'Dwyer et al, 2021; Wilson et al, 2017, 2021). What is evident from these reviews is that there are multiple challenges and knowledge gaps when integrating TIC in acute MHN roles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popper (1970, p. 53) proposes that those undertaking normal science could be considered ‘victims of indoctrination’, working within paradigms which are not accepting of novel theories. Mental health nurses are perhaps an interesting group to be considered in relation to this notion of indoctrination, as one could argue that mental health nurses are often working within , but not necessarily of biological or medical model paradigms (Isobel & Edwards, 2017; Wilson et al, 2021). In this sense, mental health nurses could be viewed as an oppressed group (Roberts et al, 2009), often working within a paradigm underpinned by an epistemology which is of limited use to them (O'Donovan, 2007).…”
Section: The Contemporary Paradigmatic Crisismentioning
confidence: 99%
“…Existing research on TIC in mental health settings has consistently reported that MHNs also experience trauma and re-traumatisation; with limited investigation into the role of the TIC model vis-à-vis these identified challenges (Isobel et al, 2020;Jacobwitz et al, 2015;Wilson et al, 2021). Notably, only a limited number of studies have exclusively centred on the implications of TIC for the MHN profession within hospital or acute mental health settings (Wilson et al, 2021(Wilson et al, , 2023. It is imperative to explore the implications of TIC on the MHN profession within this context to enhance the quality of care for people living with mental health conditions.…”
Section: Bac Kgrou N Dmentioning
confidence: 99%